Hubungan Manusia dan Penciptaan: Dekonstruksi Antroposentrisme dalam Krisis Ekologis dan Rekonstruksi dari Perpektif Eko-Teologis - Yohakim Polohae Ritan; Mario Antonius Wato Tukan; Rafael Hilarius Rangi Hurint (JURNAL ILMIAH PENDIDIKAN KEBUDAYAAN DAN AGAMA, 2026)
The gobal ecological crisis reflects the deteriorating relationship between humans and nature caused by the anthropocentric paradigm that places human at the center of life. This perspective encourages excessive exploitation of nature, resulting in inviromental destruction and ecosystem imbalance. This study aims to analyze the decontruction of anthtropocentricm within the ecological crisis and to reconstruct the relationship between humans and creation through the perspective of eco-theology. The research employs a quaitative method using a literature study approach by analizyng  various theological and ecological sources. The findings reveal that the ecological crisis is not merely a technical, but also a crisis of human paradigms toward nature. Therefore, the deconstruction of anthropocentrims is necessary to challenge the exploitative mindset of humans toward creation. Eco-theology offers an understanding that humans are an integral part of creation and possess moral and spiritual responsibilities  top reserve ecological sustainability. The relationship between humans and nature needs to be rebuilt harmoniously through ecological awareness, invironmental ethics, and collective responsibility for the sustainability of life. Thus, reconstructing the relationship between humans and creation becaomes an essential step toward developing a more ethical, sustainable, respectful awareness of all  creation.